Melatonin in Critically Ill Children - Foster, Jennifer Ruth (Journal of Pediatric Intensive Care, 2016)
Melatonin, while best known for its chronobiologic functions, has multiple effects that may be relevant in critical illness. It has been used for circadian rhythm maintenance, analgesia, and sedation, and has antihypertensive, anti-inflammatory, antioxidant, antiapoptotic, and antiexcitatory effects. This review examines melatonin physiology in health, the current state of knowledge regarding endogenous melatonin production in pediatric critical illness, and the potential uses of exogenous melatonin in this population, including relevant information from basic sciences and other fields of medicine. Pineal melatonin production and secretion appears to be altered in critical illness, though understanding in pediatric critical illness is in early stages, with only 102 children reported in the current literature. Exogenous melatonin may be used for circadian rhythm disturbances and, within the critically ill population, holds promise for diseases involving oxidant stress. There are no studies of exogenous melatonin administration to critically ill children beyond the neonatal period.
Keywords: melatonin; pineal gland; intensive care units; pediatric; critical care; circadian rhythm; antioxidants